Keefektifan Model Pembelajaran Bermain Peran untuk Meningkatkan Kemampuan Berkomunikasi pada Siswa Sekolah Dasar - Rivaldi Tri Cahyo; Iis Ristiani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The maintenance of education must be tailored to the needs and interests of students so that they learn something that interests them. Therefore, today's educational systems focus educational objectives and processes on the child's factor and can foster freedom of interests and needs. This makes the Social Science subjects taught in primary school must be based on the needs and interests of the child about the environment in which he lives. Basically, the subject of Social Science must be taught with a full sense of responsibility to the student, because it is very closely related to the people and the environment where humans live and carry out the activities to meet their needs. This makes the role of the teacher not only as a teacher but also as a guide and at the same time as an administrator. The personal teacher as a unit also determines the learning result given. Therefore, the component of the teaching situation, the correct delivery method and the media used also determine the learning outcome.Thus it can be concluded, that learning will be successful when considering many interrelated teaching components. These components can be grouped into three main categories, namely: first, the teacher, second, the subject matter, and third, the student. The interaction between the three main components involves the means and objects, methods, media and setting up of the learning environment so that a learning situation is created that enables the achievement of a previously planned goal.